Will they do it again? : risk assessment and management in criminal justice and psychiatry - Prins, Herschel A. (Routledge, 1999)
Focus in the media on the risks posed to ordinary people has become increasingly strong in recent years - particularly on those risks popularly perceived to be posed by the mentally ill. But how justified is this concern? How do we best manage so-called dangerous people? In Will They Do It Again? Herschel Prins considers the issue of public protection within a broad context of risk in society generally, examining the concerns arising in contemporary society from dealing with uncertainty. It is argued that public fear over the danger posed by the mentally ill is at odds with the ev.